Lineage‐specific evolution of cnidarian Wnt ligands. Issue 5 (14th August 2014) - Hensel, Katrin; Lotan, Tamar; Sanders, Steve M.; Cartwright, Paulyn; Frank, Uri
SUMMARY We have studied the evolution of Wnt genes in cnidarians and the expression pattern of all Wnt ligands in the hydrozoan Hydractinia echinata. Current views favor a scenario in which 12 Wnt sub‐families were jointly inherited by cnidarians and bilaterians from their last common ancestor. Our phylogenetic analyses clustered all medusozoan genes in distinct, well‐supported clades, but many orthologous relationships between medusozoan Wnts and anthozoan and bilaterian Wnt genes were poorly supported. Only seven anthozoan genes, Wnt2, Wnt4, Wnt5, Wnt6, Wnt 10, Wnt11, and Wnt16 were recovered with strong support with bilaterian genes and of those, only the Wnt2, Wnt5, Wnt11, and Wnt16 clades also included medusozoan genes. Although medusozoan Wnt8 genes clustered with anthozoan and bilaterian genes, this was not well supported. In situ hybridization studies revealed poor conservation of expression patterns of putative Wnt orthologs within Cnidaria. In polyps, only Wnt1, Wnt3, and Wnt7 were expressed at the same position in the studied cnidarian models Hydra, Hydractinia, and Nematostella. Different expression patterns are consistent with divergent functions. Our data do not fully support previous assertions regarding Wnt gene homology, and suggest a more complex history of Wnt family genes than previously suggested. This includes high rates of sequence divergence and lineage‐specific duplications of Wnt genes within medusozoans, followed by functional divergence over evolutionary time scales.